A pilot study using geospatial analysis to identify hot-spot of populations utilizing services at university based counseling centers. Issue 5 (22nd June 2022) - Patel, Rahul S.; Walker, Tanesha; Weber, Zachary T.; Kelley, Sarah D.; Hansen, Ryan
Abstract: Objective: Our pilot study tests whether university counseling centers (UCC) can apply the concept of cluster analysis, and geospatial analysis to identify clusters of "hot spots". Participants: Study participants were university students who received services from a large mid-western UCC between August 2015 and July 2016. The study was approved by the University's Institutional Review Board (IRB). Data collected include demographics, address, educational level and declared major. Methods: Data analysis, conducted using SYSTAT 13.1, IBM SPSS Statistics, ArcGIS Desktop and 10.2, ArcOnline, Microsoft excel to clean and analyze demographic data. Analysis included optimized cluster analysis with a p -value < 0.05 as statistically significant. Results: 927 participants, average age was 21.6. We identified "hotspots" using cluster analysis based on age, address, and country of origin. Conclusions: Our study shows that UCCs can apply cluster analysis, and geospatial analysis to identify clusters of "hot spots" to target risk populations.